Estimation of marginal time in water distribution systems for valve closure considering transient flow effects (2017)
Water Distribution Systems (WDS) design problem is frequently carried out under the assumption of steady state flow through the entire network. However, a disruption from steady flow conditions occurs when there is a change in operation of elements in the system as valves or pumps. By undergoing the valve operation properly, the transient pressure changes can be kept under control, minimizing its effects. This research was focused on finding the marginal time by determining a set of optimal closures of a valve at different locations in a WDS. An optimization model was used with valve closure curve and closure time as decision variables; and two objective functions were established: minimization of the Surge Damage Potential Factor (SDPF) and minimization of the Amount of Water Passed (AWP). This model was solved using NSGA II algorithm. The results obtained showed the existence of a Pareto front between SPDF and AWP for the valve operation. This front proved the existence of a marginal time in different WDS with diverse characteristics as maximum flow and existing valves. Determining the marginal time of a WDS can lead to operate different elements properly by minimizing transient flow effects